2014
DOI: 10.1080/02786826.2014.890694
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Operation of the Miniature Combustion Aerosol Standard (Mini-CAST) Soot Generator

Abstract: The Jing Ltd. miniature combustion aerosol standard (Mini-CAST) soot generator is a portable, commercially available burner that is widely used for laboratory measurements of soot processes. While many studies have used the Mini-CAST to generate soot with known size, concentration, and organic carbon fraction under a single or few conditions, there has been no systematic study of the burner operation over a wide range of operating conditions. Here, we present a comprehensive characterization of the microphysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 48 publications
11
85
0
Order By: Relevance
“…On the other hand, the Raman spectroscopy and TEM studies, presented earlier in this section, have shown that only the lean-flame samples represent the chemical structure and morphology of engine-emitted soot. Therefore, the findings of this study are in agreement with those of Moore et al (2014), with the additional basis in terms of chemical structure and morphology.…”
Section: Comparing the Size And Morphology Of Sootsupporting
confidence: 81%
See 3 more Smart Citations
“…On the other hand, the Raman spectroscopy and TEM studies, presented earlier in this section, have shown that only the lean-flame samples represent the chemical structure and morphology of engine-emitted soot. Therefore, the findings of this study are in agreement with those of Moore et al (2014), with the additional basis in terms of chemical structure and morphology.…”
Section: Comparing the Size And Morphology Of Sootsupporting
confidence: 81%
“…From Table 1 of Moore et al (2014), it can be concluded that high-OC soot generated under fuel-lean conditions represent the properties of aircraft-emitted soot better that the other two operating regimes. To compare the results of the present work with those of Moore et al, the EC-to-TC ratios of soot samples studied herein are shown in Tables S3 and S4 in the SI.…”
Section: Comparing the Size And Morphology Of Sootmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate this assumption, and to develop a more repeatable process for creating transfer standards, quartz-fiber filter samples with increased loadings were prepared from laboratory-generated aerosols using a diesel generator, flaming dry pine needles, smoldering damp pine cones, and smoldering Florida peat. Other potential transfer standards might be obtained from graphite electric arc soot (Evans et al, 2003), resuspended carbon black or graphite powders (Medalia and Richards, 1972;Jäger et al, 1999), or a lean-burning gas torch Chow et al, 2009;Moore et al, 2014), but these are dominated by BC and do not include a major BrC component. Diesel exhaust was generated by an Onan Cummins 12.5 kW diesel generator with an accumulated 2,500 hours operating on commercial diesel fuel (< 15 ppmw sulfur content) under idling conditions.…”
Section: Changes To Carbon Analyzers and Proceduresmentioning
confidence: 99%